The Effect of Enzyme Supplementation on Apparent Ileal Amino Acid Digestibility of Broilers Fed Sorghum or Wheat - NGA Mulyantini; WL Bryden (Animal Production: Indonesian Journal of Animal Production, 2010)
In plant products such as sorghum and wheat, 50-70% of total phosphorus is bound in the form of phytin-P, which is unavailable to poultry due to the lack of significant endogenous production of the enzyme phytase. As a consequence, nitrogen retention and amino acid utilisation are reduced due to the reduction in protein digestibility. The objective of this study was to determine the influence of a commercial xylanase and phytase alone and in combination on the apparent amino acid digestibility of wheat and sorghum. The experimental diets were fed in mash form to three replicate pens (6 male birds per pen) for 5 days. On day 42, all birds were euthanatised by an intracardial injection of sodium pentabarbitone solution, and the contents of the lower half of the ileum were collected. Amino acid concentration of ileal digesta samples was determined. The enzymes used were: natuphos phytase (5,000 FTU/g), xylanase (55,000 EXU/g) and b-glucanase (1,200 BGU/g) as well as several side- activities (cellulase and protease); the recommended inclusion rate is 120 g/tonne. Analyses were performed using statistical analysis software SAS. In conclusion, inclusion of xylanase alone in wheat based broiler diets is advantageous through positive effects on the digestibility of all amino acids. In sorghum based diets, there was no improvement in amino acid digestibility with xylanase or phytase supplementation. (Animal Production 12(3): 169-174 (2010)Key Words : amino acid, digestibility, enzyme, wheat, sorghum